2020
DOI: 10.18438/eblip29630
|View full text |Cite
|
Sign up to set email alerts
|

Information Literacies of PhD Students in the Health Sciences: A Review of Scholarly Articles (2009 - 2018)

Abstract: Abstract Objective – Doctoral studies offer a unique phase in the development and legitimization of researchers, in which PhD students shift from the consumption to the production of knowledge. If librarians are to support this process in an evidence based manner, it is essential to understand the distinct practices of this user population. While recent reviews exist concerning the information behaviours of graduate students and researchers, there is little knowledge synthesis focused on the information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…A narrative review with the purpose of investigating changes in PhD students' information seeking behaviours, also found that most studies grouped PhD students together with other graduate students or with other researchers (Spezi, 2016). In our own review of scholarly articles published between 2009 and 2018, only 0.3% of the initial data set (7 of 2317 records) directly addressed the information literacies of PhD students within the health sciences (Nylander & Hjort, 2020).…”
Section: Information Literacies Of Phd Students Within the Health Scimentioning
confidence: 79%
“…A narrative review with the purpose of investigating changes in PhD students' information seeking behaviours, also found that most studies grouped PhD students together with other graduate students or with other researchers (Spezi, 2016). In our own review of scholarly articles published between 2009 and 2018, only 0.3% of the initial data set (7 of 2317 records) directly addressed the information literacies of PhD students within the health sciences (Nylander & Hjort, 2020).…”
Section: Information Literacies Of Phd Students Within the Health Scimentioning
confidence: 79%